The transcriptional coactivator Bob1 promotes the development of follicular T helper cells via Bcl6. (8th March 2016) - Stauss, Dennis; Brunner, Cornelia; Berberich‐Siebelt, Friederike; Höpken, Uta E; Lipp, Martin; Müller, Gerd
Abstract: Follicular T helper (Tfh) cells are key regulators of the germinal center reaction and long‐term humoral immunity. Tfh cell differentiation requires the sustained expression of the transcriptional repressor Bcl6; however, its regulation in CD4 + T cells is incompletely understood. Here, we report that the transcriptional coactivator Bob1, encoded by the Pou2af1 gene, promotes Bcl6 expression and Tfh cell development. We found that Bob1 together with the octamer transcription factors Oct1/Oct2 can directly bind to and transactivate the Bcl6 and Btla promoters. Mixed bone marrow chimeras revealed that Bob1 is required for the expression of normal levels of Bcl6 and BTLA, thereby controlling the pool size and composition of the Tfh compartment in a T cell‐intrinsic manner. Our data indicate that T cell‐expressed Bob1 is directly involved in Tfh cell differentiation and required for mounting normal T cell‐dependent B‐cell responses. Synopsis: Follicular T helper (Tfh) cells are essential for B cell‐mediated immunity. Tfh cell differentiation and the maintenance of the Tfh phenotype require continuous expression of high levels of Bcl6. Bob1 enhances the expression of Bcl6 in CD4 + T cells, a master regulator of Tfh cell differentiation. Bob1 is an important driver for the expression of B and T lymphocyte attenuator (BTLA, CD272) on Tfh cells. Together with Oct1/2, Bob1 can directly bind to and transactivate the Bcl6 and Btla promoters. Bob1 promotes Tfh cell differentiation and appears to fine‐tune the immune response following immunization with a protein antigen. Abstract : Expression of the master Tfh cell differentiation factor Bcl6 is controlled by Bob1 and Oct1/2 transcription factors, to fine‐tune B‐cell responses following antigen‐mediated immunization.